Long-term Normothermic Machine Preservation of Partial Livers: First Experience With 21 Human Hemi-livers. Issue 5 (29th November 2021) - Mueller, Matteo; Hefti, Max; Eshmuminov, Dilmurodjon; Schuler, Martin J.; Sousa Da Silva, Richard X.; Petrowsky, Henrik; De Oliveira, Michelle L.; Oberkofler, Christian E.; Hagedorn, Catherine; Mancina, Leandro; Weber, Achim; Burg, Brian; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to maintain long-term full function and viability of partial livers perfused ex situ for sufficient duration to enable ex situ treatment, repair, and regeneration. Background: Organ shortage remains the single most important factor limiting the success of transplantation. Autotransplantation in patients with nonresectable liver tumors is rarely feasible due to insufficient tumor-free remnant tissue. This limitation could be solved by the availability of long-term preservation of partial livers that enables functional regeneration and subsequent transplantation. Methods: Partial swine livers were perfused with autologous blood after being procured from healthy pigs following 70% in-vivo resection, leaving only the right lateral lobe. Partial human livers were recovered from patients undergoing anatomic right or left hepatectomies and perfused with a blood based perfusate together with various medical additives. Assessment of physiologic function during perfusion was based on markers of hepatocyte, cholangiocyte, vascular and immune compartments, as well as histology. Results: Following the development phase with partial swine livers, 21 partial human livers (14 right and 7 left hemi-livers) were perfused, eventually reaching the targeted perfusion duration of 1 week with the final protocol. These partial livers disclosed a stable perfusion with normal hepatic function including bile production (5–10 mL/h), lactate clearance, and maintenance of energy exhibited by normal of adenosine triphosphate (ATP) and glycogen levels, and preserved liver architecture for up to 1 week. Conclusion: This pioneering research presents the inaugural evidence for long-term machine perfusion of partial livers and provides a pathway for innovative and relevant clinical applications to increase the availability of organs and provide novel approaches in hepatic oncology.